Morphometric analyses of the Paracentral Lobe. - Oliveira Neto, Moacyr; Nascimento, Payron Augusto; Rodrigues, Renan Barbosa; Machado, William Browne de Oliveira; Oliveira, Lean de Sousa; Silva Filho, Antônio Ribeiro da (Journal of Health & Biological Sciences, 2014)
Introduction:There are no studies that evaluate measurements of the distances between the grooves that delimit the Paracentral Lobule (PCL) in the literature. This study seeks to contribute to the knowledge regarding the anatomy of the PCL, conducting an analysis of morphometric measurements in this region and its correlation with the paracentral sulcus, marginal branch of the cingulate and central sulcus. Methods:42 hemispheres were evaluated, 20 were right and 22 left. Using digital caliper Dc - 6 Western ®, measurements of the size of PCL in the sagittal axis and coronal axis were made, in addition to measures of the Central Sulcus to the Paracentral Sulcus (motor area) and Central Sulcus to Marginal Branch of the Cingulate Sulcus (somesthetic area), comparing the prevalence of each of these lengths between hemispheres. Results:The average length between the Paracentral Sulcus and the Central Sulcus was 24.49 cm(14.2 to 38.6 cm) in the right hemisphere and 25.50 cm(11.7 to 37.0 cm) in the left. As between the Central Sulcus and the Marginal Branch of the Cingulate Sulcus was in average 10.03 cm(2.6 to 22.7 cm) in the right and in the left PCL 9.17cm(2.6 to 22.7 cm). In the right hemisphere, 19 samples(86,4%) presented greater motor area than somesthetic and, in the left hemisphere, 19 samples(95%) had greater motor area. Conclusion:The motor area showed prevalence in relation to the sensory area in the analysis of the two hemispheres, while the comparison of other measures between the two hemispheres showed no significance.